Firm-level internationalisation and the home bias puzzle - KEARNEY, COLM; BERRILL, JENNY (Elsevier, 2010)
The extent to which internationalising MNEs create value, and the extent to which investors can reap the benefits of firm-level internationalisation remain controversial issues. Using a multi-country dataset with over 3 million observations, we classify 1,143 firms listed on the exchanges of the G7 countries according to the geographical spread of their sales and subsidiaries. We show that more internationalised firms provide greater diversification benefits. By investing in home-based internationalised firms, investors can `free ride? the costs and risks associated with internationalisation at the level of the firm and exhibit home bias while availing of international diversification benefits.
PUBLISHED
Keywords: Economics and business; International diversification